Management Accounting for Profit Control, Second Edition. - Singer, Frank A.; Griffin, Charles H. (The Accounting Review, 1966)
The article reviews the book "Management Accounting for Profit Control," second edition, by I. Wayne Keller and William L. Ferrara.